INOVASI PRODUK DAN LAYANAN KEUANGAN SYARIAH DI ERA DIGITAL - Takwim, Ahsani; Lestari, Dinda; Maharani, Filiya Novita; Prasetya, Iip; Anggraeni, Lasnia Sisma (Pusat Riset dan Publikasi, 2024)
The advancement of digital technology has caused significant changes in many industries, including the Islamic banking sector. The digital era has created new opportunities for sharia banks to innovate in developing products and services that are more accessible, efficient, and in accordance with Islamic principles. This research uses a qualitative method with a literature study approach. Literature sources can be obtained from books, journals, magazines, research results (thesis and dissertation), and other relevant sources (internet, newspapers, etc.). The research findings showed that innovation of products and services related to sharia finance in the digital era has significant potential to increase financial accessibility, improve operational efficiency, increase transparency, develop products and services that are more in line with the needs of micro, small, medium and large enterprises, and increase awareness of financial products. This article provides guidance on how to improve innovation of products and services related to sharia banking in the digital era, such as improving more personalized products and services, improving standards of financial education and literacy.